FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN YANG LISTED DI BEI - Nofa Ariani, Fitria; Widodo, Agustina (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This research aims to prove and analyze the impact of profitability, leverage, firm size and dividend policy on firm value in textile and garment sub-sector manufacturing companies listed on the IDX. Purposive sampling was used in selecting the sample used in this research. Analysis of proving the hypothesis in this research was carried out using multiple linear regression analysis. The research results prove profitability and dividend policy partially have a significant positive impact on firm value. While the leverage variable has a significant negative impact and firm size has a positive but not significant impact on firm value. The value of adjusted R2 is 0.397, so it can be interpreted that 39.7 percent of the firm value variation in textile and garment sub-sector manufacturing companies listed on the IDX can be explained by the four independent variables, namely profitability, leverage, firm size and dividend policy. On the other hand, 60.3 percent is explained by other variables not examined in this research.